9514 1404 393
Answer:
-12, -21
Step-by-step explanation:
Let x represent the first number. Then the second is x-9. The other relation is ...
4x = 2(x-9) -6
2x = -24 . . . . . subtract 2x, simplify
x = -12
x-9 = -21
The first number is -12; the second number is -21.
The B option is the correct answer
True the variable in the expression is y
Answer:
It's proved below
Step-by-step explanation:
We are given;
- K is the midpoint of JL
- M is the midpoint of LN
By definition of mid points, we can say that;
JK = KL and LM = MN
Now, we are given that JK = MN.
Thus, by substitution, we can deduce that; KL = LM
Thus is because JK can be replaced with KL and MN can be replaced with LM.
Thus, it is proved that KL = LM
Answer:
Step-by-step explanation:
It would be more obvious if it says z is a standard Normal variable and that the question is related to statistics.
From "Computing Probabilities Using the Cumulative Table" , the probability of z is less than 1.16, P(z<1.16) = 0.8770.